THE ROLE OF THE HOLY CROSS CHURCH IN THE DEVELOPMENT OF THE CAUCASIAN DIOCESE IN THE MIDDLE OF THE XIX CENTURY - P. Nemashkalov (Гуманитарные и юридические исследования)
For the first time the article, with the reference to a wide range of archival sources, introduces into scientific circulation the history of the foundation of the Holy Cross Church of the Caucasian Episcopal House and its role during the formation of an independent Caucasian diocese. The relevance of this topic is related to the fact that the construction of this temple coincided with one of the most difficult stages in the development of the diocese itself. All the challenges faced by the Caucasian Diocese in the conditions of the North Caucasus reality, are reflected in the structure of this temple. In the current situation with the existing monasteries within the Caucasian Diocese, which due to objective conditions could not accept disobedience from the clergy, they were assigned to the Episcopal house and passed obedience to the Holy Cross Church. Having a high administrative diocesan status, being an exemplary episcopal church, the Holy Cross Church had a great influence on the development of parish life and the evolution of church culture in the North Caucasus. In church parishes, diocesan authorities quite often put up with the fact that in rural parish life, the high demands of the Orthodox canon were rarely fully realized not only by parishioners, but also by church clergy. The church authorities paid special attention to all sorts of incidents, in which the administration of the consistory was bogged down and in respect of which strict measures were taken. A certain role in solving current issues on the ground was assigned to the Provost, but the inal decision was made by the diocesan consistory. Because of the beginning of large-scale reforms in all areas of the church life of the Caucasian diocese, a conflict arose around the church life in the region and the Cossack liberties. Not accepting compromise solutions, Bishop Jeremiah (Soloviev) was drawn into the state's experiment on the assertion of a single-religion church in the region, the reason for which was the complaint of the Grebian Cossacks. The result of this conflict was the division of the Caucasian Diocese, and as history shows later, it will be unsuccessful and will serve as a pretext for its uniication and revision by the state of church policy in the North Caucasus. However, the missed opportunities for the normalization of church life in the parishes of the diocese at this stage of its development cannot be replenished in the subsequent period of its development.